Association of glucose tolerance status with pancreatic β‐ and α‐cell mass in community‐based autopsy samples of Japanese individuals: The Hisayama Study. Issue 5 (10th March 2020) - Inaishi, Jun; Saisho, Yoshifumi; Hirakawa, Yoichiro; Yoshida, Daigo; Hata, Jun; Mukai, Naoko; Watanabe, Yuusuke; Oda, Yoshinao; Itoh, Hiroshi; Ninomiya, Toshiharu
Abstract: Aims/Introduction: Changes in histologically quantified β‐ and α‐cell mass during the development of glucose intolerance have not been fully elucidated. The aim of the present study was to explore differences in β‐ and α‐cell mass according to the glucose tolerance status. Materials and Methods: Autopsy samples from a total of 103 individuals (40 with normal glucose tolerance, 31 with prediabetes and 32 with type 2 diabetes mellitus) who underwent a 75‐g oral glucose tolerance test within 5 years before death were selected from 643 community‐based autopsy samples collected from 2002 to 2016. Fractional β‐cell area (BCA) and α‐cell area were quantified with Image Pro Plus software. Associations of BCA and α‐cell area with glucose tolerance status were assessed using a linear regression analysis, and Spearman's correlation coefficients between glycemic markers and β‐cell function were estimated. Results: The mean values of BCA decreased significantly with worsening glucose tolerance status (mean ± standard error 1.85 ± 0.10% in normal glucose tolerance, 1.59 ± 0.11% in prediabetes and 1.17 ± 0.11% in type 2 diabetes mellitus, P for trend < 0.001), whereas there was no significant association between α‐cell area and glucose tolerance status. BCA was inversely correlated with fasting and 2‐h plasma glucose levels during oral glucose tolerance test and glycated hemoglobin measurement, and positively correlated with disposition index (all P < 0.01). Conclusions: β‐Cell mass decreased significantly with worsening glucose tolerance, from the stage of prediabetes, in the Japanese population. Prevention of declining β‐cell mass before the onset of glucose intolerance is important to reduce the burden of type 2 diabetes mellitus. Abstract : A lower fractional β‐cell area was associated significantly with the deterioration of glucose tolerance status in community‐based autopsy samples of Japanese individuals.